2021
DOI: 10.1055/a-1543-1261
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoids from Alisma orientale and their NF-кB Inhibitory Activity

Abstract: The rhizome of Alisma orientale (sam.) Juz. is used in clinics for eliminating dampness, reducing edema, and promoting diuresis. This study aimed to elucidate the compounds and investigate their nuclear factor-kappa inhibitory activities in human embryonic kidney 293 cells. A new triterpene, alismaketone B (1); a new natural nortriterpene, noralisolic acid A (2); and 13 known protostane-type triterpenes were isolated from the rhizome of A. orientale. The new structures and their absolute configurations were es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…Rhizoma alismatis has a long history of use in China and exhibits physiological activities, such as diuretic, anti-urolithiasis, antioxidant, and anti-inflammatory characteristics [29,30]. Du et al [31] showed that R. alismatis extract is almost nontoxic to cells at low concentrations, and that adding it to oleic acid-treated hepatocytes could reverse the lipid peroxidation in hepatocytes and reduce the expression of cellular inflammatory factors, as well as the degree of cell damage.…”
Section: Introductionmentioning
confidence: 99%
“…Rhizoma alismatis has a long history of use in China and exhibits physiological activities, such as diuretic, anti-urolithiasis, antioxidant, and anti-inflammatory characteristics [29,30]. Du et al [31] showed that R. alismatis extract is almost nontoxic to cells at low concentrations, and that adding it to oleic acid-treated hepatocytes could reverse the lipid peroxidation in hepatocytes and reduce the expression of cellular inflammatory factors, as well as the degree of cell damage.…”
Section: Introductionmentioning
confidence: 99%